Optimizing Employee Performance and Performance Appraisal Through Job Satisfaction - Khuzaini; Zamrudi, Zakky; Madihah, Husnul (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to analyze the effect of performance appraisal on employee performance, with job satisfaction as a mediating variable. A quantitative approach was employed using a survey method involving 161 private sector employees from three major districts in South Kalimantan Province. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that performance appraisal does not have a significant direct effect on employee performance but does significantly affect job satisfaction. Job satisfaction also has a significant impact on employee performance and mediates the relationship between performance appraisal and employee performance. These findings suggest that a well-designed performance appraisal system can enhance job satisfaction, which in turn positively influences employee performance. The practical implications of this study highlight the importance of organizations designing performance appraisal systems that not only assess but also develop employees. Theoretically, this study reinforces the understanding of the mediating role of job satisfaction in the relationship between performance appraisal and employee performance and contributes to the advancement of human resource management practices.